A power cycle of natural gas decarbonization and dual fuel cells with inherent 100% carbon capture. (27th September 2018) - Zhuang, Quan; Geddis, Phil; Runstedtler, Al; Clements, Bruce
Abstract: An integrated natural gas decarbonisation and dual fuel cells power cycle (NGDDFC) was evaluated. The hydrogen and solid carbon produced in the natural gas decarbonisation process are fed to hydrogen and carbon fuel cells respectively. A fraction of the produced hydrogen is combusted to supply the heat required for natural gas decarbonisation. A pure carbon dioxide stream is produced from the carbon fuel cell, suitable for sequestration. The power cycle shows an efficiency of about 61% with near 100% carbon capture, 15 to 20% points higher than natural gas combined cycle (NGCC). Highlights: An advanced natural gas dual fuel cell system is proposed. Natural gas decarbonisation followed by a hydrogen fuel cell and a carbon fuel cell. Anode exhaust from carbon fuel cell is a pure CO2, ready for sequestration. A fraction of hydrogen is burnt to supply heat for natural gas cracking. The power cycle has an efficiency of 61% (HHV of natural gas) with 100% carbon capture.